2019
DOI: 10.1093/jac/dkz349
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to piperacillin/tazobactam in Escherichia coli resulting from extensive IS26-associated gene amplification of blaTEM-1

Abstract: Background bla TEM-1 encodes a narrow-spectrum β-lactamase that is inhibited by β-lactamase inhibitors and commonly present in Escherichia coli. Hyperproduction of blaTEM-1 may cause resistance to penicillin/β-lactamase inhibitor (P/BLI) combinations. Objectives To characterize EC78, an E. coli bloodstream isolate, resistant to P/BLI combinations, which contains extensive amplification of blaTEM-1 within the chromosome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 19 publications
3
64
0
Order By: Relevance
“…Tazobactam is able to inhibit the activity of class A β-lactamases [39], and therefore the presence of bla TEM-1 within the genome of an E. coli isolate should not result in resistance to TZP. However, two studies have linked amplification of bla TEM , and therefore hyperproduction of the BL, with this phenotype [15, 18], with one linking amplification and the presence of IS 26 [18]. However, the exact mechanism of amplification/hyperproduction has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tazobactam is able to inhibit the activity of class A β-lactamases [39], and therefore the presence of bla TEM-1 within the genome of an E. coli isolate should not result in resistance to TZP. However, two studies have linked amplification of bla TEM , and therefore hyperproduction of the BL, with this phenotype [15, 18], with one linking amplification and the presence of IS 26 [18]. However, the exact mechanism of amplification/hyperproduction has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al 2019 associated amplification of bla TEM-1 in E. coli clinical isolate with a significant fitness cost [18];Fitness of this isolate was compared to other unrelated clinical isolates of E. coli which hyperproduced Bla TEM-1 due to promoter mutations, rather than the same isolate with and without amplification. This approach can lead to over- or under-estimation of fitness cost, as genetic background of the isolate can have an impact on the overall fitness affect, as can the environment fitness is assessed in [45, 46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, van Boxtel et al demonstrated that serial passaging of an ESBL or AmpC-producing isolate in the presence of a carbapenem can result in amplification of plasmid-borne β-lactamase genes (7). Increased expression of the narrow-spectrum TEM β-lactamases has similarly been reported to result in cefepime (8) and piperacillin-tazobactam resistance (911), indicating that β-lactamase gene dosage is a factor in increasing resistance to multiple β-lactam chemotherapies. These findings demonstrate expression level and copy number of β-lactamases without known carbapenemase activity have important effects on carbapenem susceptibility in porin deficient backgrounds (6, 7).…”
Section: Introductionmentioning
confidence: 99%